1994
DOI: 10.1182/blood.v83.11.3403.3403
|View full text |Cite
|
Sign up to set email alerts
|

Development of a retroviral construct containing a human mutated dihydrofolate reductase cDNA for hematopoietic stem cell transduction

Abstract: A double-copy Moloney leukemia virus-based retroviral construct containing both the NeoR gene and a mutant human dihydrofolate reductase (DHFR) cDNA (Ser31 mutant) was used to transduce NIH 3T3 and mouse bone marrow (BM) progenitor cells. This resulted in increased resistance of these cells to methotrexate (MTX). The transduced BM progenitor cells were returned to lethally irradiated mice. The recipients transplanted with marrow cells infected with the recombinant virus showed protection from lethal MTX toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…DHFR was first tested for its ability to protect BM cells in vivo. HSCs transduced with DHFR variants become resistant to antifolate agents, such as methotrexate and trimetrexate (Li et al, 1994;Spencer et al, 1996), and can be positively selected both in vitro and in vivo. DHFR naturally functions to generate tetrahydrofolate, which is necessary for the de novo synthesis of pyrimidines and purines.…”
Section: Hscs In Vivo Selection Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DHFR was first tested for its ability to protect BM cells in vivo. HSCs transduced with DHFR variants become resistant to antifolate agents, such as methotrexate and trimetrexate (Li et al, 1994;Spencer et al, 1996), and can be positively selected both in vitro and in vivo. DHFR naturally functions to generate tetrahydrofolate, which is necessary for the de novo synthesis of pyrimidines and purines.…”
Section: Hscs In Vivo Selection Strategiesmentioning
confidence: 99%
“…This has been achieved by genes/factors that could confer on HSCs a growth advantage or would allow for their in vivo selection. A number of genes encoding drug-resistance molecules are currently under investigation, such as the human dehydrofolate reductase (DHFR), multi-drug resistance 1 (MDR1), and 53 methylguanine metyltransferase (MGMT) drug-resistance genes (Allay et al, 1998;Chinnasamy et al, 1998;Davis et al, 2000;Hickson et al, 1998;Li et al, 1994;Persons et al, 2003;Sawai et al, 2001;Spencer et al, 1996). A side effect to this strategy is the high toxicity of the selective drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, vectors containing mutated DHFR genes have been engineered for transduction of hematopoietic progenitor cells [47][48][49]. Williams et al [50] and Cline et al [51] demonstrated protection of recipient animals from lethal doses of methotrexate.…”
Section: Animal Models For Transduction Of Chemoresistance Genes To Hmentioning
confidence: 99%
“…The four-week delay allowed selection with a much larger dose of MTX. The delayed high dose selection with MTX resulted in deaths of all control animals within four weeks while more than 80% of experimental animals survived the treatment [48]. Presently we are investigating other clinically suitable protocols such as BMT without the need for prior whole body irradiation of the recipients so that the whole procedure can be made less hazardous.…”
Section: Transduction Of Murine Bone Marrow By Coculture Of Bone Marrmentioning
confidence: 99%